RNA Profiling Reveals a Common Mechanism of Histone Gene Downregulation and Complementary Effects for Radioprotectants in Response to Ionizing Radiation. Issue 4 (15th October 2020) - Ge, Changhui; Su, Fei; Fu, Hanjiang; Wang, Yuan; Tian, Baolei; Liu, Bin; Zhu, Jie; Ding, Yong; Zheng, Xiaofei
High-dose ionizing radiation (IR) alters the expression levels of non-coding RNAs (ncRNAs). However, the roles of ncRNAs and mRNAs in mediating radiation protection by radioprotectants remain unknown. Microarrays were used to determine microRNA (miRNA), long ncRNA (lncRNA), and mRNA expression profiles in the bone marrow of irradiated mice pretreated with amifostine, CBLB502, and nilestriol. Differentially expressed mRNAs were functionally annotated by Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway analyses. Some histone cluster genes were validated by real-time PCR, and the effects of radioprotectant combinations were monitored by survival analysis. We found that these radioprotectants increased the induction of lncRNAs and mRNAs. miRNA, lncRNA, and mRNA expression patterns were similar with amifostine and CBLB502, but not nilestriol. The radioprotectants exhibited mostly opposite effects against IR-induced miRNAs, lncRNAs, and mRNAs while inducing a common histone gene downregulation following IR, mainly via nucleosome assembly and related signaling pathways. Notably, the effects of nilestriol significantly complemented those of amisfostine or CBLB502; low-dose drug combinations resulted in better radioprotective effects in pretreated mice. Thus, we present histone gene downregulation by radioprotectants, together with the biological functions of miRNA, lncRNA, and mRNA, to explain the mechanism underlying radioprotection.